Strategi Guru PAUD dalam Memanfaatkan Aplikasi Video Konferensi Untuk Meningkatkan Kualitas Pembelajaran PAUD pada Masa Pandemi Covid-19 - Muhaimah Bishalihah (Yayasan Sahabat Literasi Edukasi dan Publikasi Bandung, 2023)
The Covid-19 pandemic, which was declared an emergency condition in Indonesia, has an impact on the education sector, the government issued a new policy regarding distance learning from early childhood to college levels. The purpose of this research is to find out the ability of teachers to use video conferencing applications, the intensity of teachers in using video conferencing applications, the efforts of teachers in utilizing video conferencing applications to improve the quality of learning. The research method chosen by the researcher is descriptive qualitative naturalistic research method. The collection techniques used by researchers are interviews, observation and documentation. The data obtained by researchers came from Ashofiah Kindergarten and RA Syifaaush Shuduur in Bojongloa Kidul District, Bandung City. The data processing technique carried out by researchers is by reducing data, displaying data and finally verifying data. The results showed that the ability of PAUD teachers to use video conference applications was still low, the intensity of PAUD teachers in using video conference applications was less than 10%. Efforts made by teachers as a distance learning media do not use video conferencing applications, the use of video conferencing applications at the PAUD level has no impact on the quality of PAUD learning